2018
DOI: 10.1111/jvh.13039
|View full text |Cite
|
Sign up to set email alerts
|

Improved liver transplant waitlist mortality and lower risk of disease progression among chronic hepatitis C patients awaiting liver transplantation after the introduction of direct‐acting antiviral therapies in the United States

Abstract: Summary Direct‐acting antiviral (DAA) therapies for chronic hepatitis C virus (HCV) infection achieve high cure rates, reducing HCV‐related disease progression to cirrhosis and hepatocellular carcinoma. We aim to evaluate the impact of DAAs on US liver transplant (LT) waitlist outcomes. We retrospectively evaluated US adults (age ≥18) with and without chronic HCV listed for LT before and after the widespread use of sofosbuvir, allowing a 6‐month period after approval (Era 1: 1/1/2002‐5/31/2014 vs Era 2: 6/1/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Through linked data, we identified a decline in HCV-associated liver transplant rates after 2014, consistent with unlinked published data for England [2,8] and internationally [9-11]. A separate study within the UK [8], using unlinked data, reported registered transplants for patients with HCV-related cirrhosis fell from 10.5% in 2013 to 4.7% in 2016.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Through linked data, we identified a decline in HCV-associated liver transplant rates after 2014, consistent with unlinked published data for England [2,8] and internationally [9-11]. A separate study within the UK [8], using unlinked data, reported registered transplants for patients with HCV-related cirrhosis fell from 10.5% in 2013 to 4.7% in 2016.…”
Section: Discussionsupporting
confidence: 79%
“…Vaziri et al reported that the proportion of liver transplants attributed to HCV-associated cirrhosis fell from 10.5% to 4.7% between 2013 and 2016 and the proportion of liver transplants for cancer-associated HCV fell from 46.4% to 33.7% over the same period [8]. Similar results have been found in Italy, the United States (US) and Argentina [9-11]. A declining contribution of HCV-associated cirrhosis and cancer to transplants is helpful but is not a substitute for monitoring rates of HCV-associated transplants and may be limited by under-reporting of HCV coding in the liver transplant dataset, as has been observed in death registry data [12].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Education regarding the potential consequences of disease progression in the absence of treatment is also important, especially as a fear of treatment or side effects was associated with a longer disease duration in this study. The latter increases the risk of serious complications of CHC infection, such as hepatic decompensation or hepatocellular carcinoma [17,45,46]. In this real-world study, 28% of the documented patients with chronic HCV infection did not receive indicated CHC treatment, despite the availability of effective pangenotypic interferon-free DAAs.…”
Section: Plos Onementioning
confidence: 88%
“…Introduction of highly effective and tolerable direct-acting antivirals (DAA) has improved waitlist mortality and lowered risk of disease progression among chronic hepatitis C virus (HCV) patients awaiting liver transplantation (LT) [1]. Optimal timing of DAA therapy in waitlist active candidates remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%